2011
DOI: 10.1056/nejmoa1008108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occult Metastases on Survival in Node-Negative Breast Cancer

Abstract: BACKGROUND-Retrospective and observational analyses suggest that occult lymph-node metastases are an important prognostic factor for disease recurrence or survival among patients with breast cancer. Prospective data on clinical outcomes from randomized trials according to sentinel-node involvement have been lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
203
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(240 citation statements)
references
References 18 publications
18
203
2
11
Order By: Relevance
“…However, the reduction in OS was marginal (0.6% at 5-years) and insufficient to justify routine analysis of deeper tissue sections or IHC for conventionally negative SLNs. Furthermore, subgroup analysis confirmed that ITCs had less impact than MM on every outcome evaluated, supporting the current segregation of categories and arguing against the need for any change in the management of women with SLN ITC [51].…”
Section: Significance Of Isolated Tumour Cells Evidence Againstmentioning
confidence: 60%
“…However, the reduction in OS was marginal (0.6% at 5-years) and insufficient to justify routine analysis of deeper tissue sections or IHC for conventionally negative SLNs. Furthermore, subgroup analysis confirmed that ITCs had less impact than MM on every outcome evaluated, supporting the current segregation of categories and arguing against the need for any change in the management of women with SLN ITC [51].…”
Section: Significance Of Isolated Tumour Cells Evidence Againstmentioning
confidence: 60%
“…23 Other studies have reported increased detection of occult metastases by similar methods, ranging from 9% to 33%. [24][25][26][27] Several markers, including cytokeratin AE1/AE3, pancytokeratin, CAM5.2, MAK-6, epithelial membrane antigen, MUC1, and cytokeratin 19, have been utilized in immunohistochemical evaluation of axillary sentinel lymph nodes. [28][29][30][31][32] Likewise, new rapid cytokeratin immunohistochemistry techniques have recently emerged that have been reported to accurately assess the sentinel lymph node intraoperatively more quickly than previous methods.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, the impact of these findings on clinical outcome is debatable, and it has been suggested that the clinical benefit of such additional evaluation, 18 including immunohistochemistry, in some cases may be limited. 23,24 Similar to these other organs, immunohistochemical evaluation of lymph nodes for occult metastases may be of value in directing prognosis and therapy for germ cell tumor patients who undergo retroperitoneal lymph node dissection, particularly if cases are categorized according to clinical suspicion. In this study, we identified additional positive lymph nodes using OCT4 immunohistochemistry that were previously interpreted as negative by light microscopy, although only in cases in which metastases had already been diagnosed by light microscopy in other lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…ITCs are categorized into pN0, and in breast cancer, micrometastasis are treated as pN0, because further axillary LN dissection is not recommended when micrometastasis is identified in sentinel LNs. The guideline was supported by a series of reports, including evaluation with the B-32 protocol by Weaver et al (3). They examined ITC/ micrometastasis on survival in 3,887 patients with breast cancer who randomly assigned to sentinel LN biopsy plus axillary dissection or sentinel LN biopsy alone.…”
mentioning
confidence: 99%